The State of Stroke Rehabilitation Design in Australia: A Multi-Scalar Systematic Architecture Precedent Review - Tianyi Yang; Marcus White; Ruby Lipson-Smith; Mehrnoush Latifi (Buildings)
Objectives: This study explores stroke rehabilitation facility design in Australia, identifying the key design typologies at multiple scales and assessing them against the critical design criteria for stroke rehabilitation. Background: The physical environment plays a crucial role in stroke rehabilitation, affecting patient recovery and well-being. However, limited research examines how design can support therapeutic outcomes in these facilities. Method: From a systematic review of 257 Australian stroke rehabilitation facilities, 30 were selected for detailed design review, with an in-depth room-level analysis conducted for 10. Using the modified PRISMA framework and a typology analysis approach, this study integrates architectural precedent with clinical research methods. Results: Typologies were identified at the site, building, ward, and room levels. Acute hospital wards (53%) and ‘blocks’ (73%) were the most common site and building arrangements, respectively. At the ward level, ‘racetrack with courtyard’ layouts enhanced natural light, views, and access to landscaped areas. A room-level analysis revealed limited innovation, with most rooms adhering to standard designs, though some adaptations improved visual connectivity and personal control. Hybrid nurse stations and courtyards supported efficiency, social interaction, and therapeutic stimulation. Conclusions: This study highlights the user-centred design strategies tailored to stroke patients’ needs and the importance of evidence-based approaches prioritising well-being. Future research should incorporate 3D spatial analysis for actionable design recommendations.